Visitor’s experiential attributes and revisit intention to Islamic tourism attractions in Malaysia / Arni Abdul Gani, Mazlina Mahdzar and Nor Asmalina M. Anuar - Abdul Gani, Arni; Mahdzar, Mazlina; M. Anuar, Nor Asmalina (Universiti Teknologi MARA Cawangan Selangor and UiTM Press, 2019)
The popularity of Malaysia as one of the prominent Islamic tourism and Muslim-friendly destinations in the world is non-arguable. The country has been recognised as one of the top destinations for Muslim travellers, owing to many factors such as world-class tourism infrastructures, nature wonders, multicultural identity, and unique culture and heritage based on the Islamic principles. The city’s most iconic Islamic attractions, the National Mosque and Islamic Arts Museum were named as must-see attractions in the city, promoted heavily by the government and have ever since experiencing a tremendous increase in visitors’ arrival. To keep up with the demand, these places need to continuously provide excellent facilities and services as expected by the tourists, and at the same time maintain the exclusivity of what an Islamic tourism attraction should be. It is essential to acknowledge that the success of any tourism attractions depends significantly on many factors, and these include its worthiness for repeat visitation. This study intends to discover the visitors’ experience of these places and assess their likelihood to make repeat visitation to the same place. Results revealed that escapism, entertainment, and aesthetic are the experiences that affect visitors’ revisit intention. Education, on the other hand, is found to have a weak relationship, prompting for further examination. Overall, the study provides an avenue for more researches to be conducted in multiple elements of these prominent Islamic tourism attractions in the country.